2008
DOI: 10.1080/02699050801895431
|View full text |Cite
|
Sign up to set email alerts
|

Early and delayed auditory oddball ERPs and brain MRI in patients with MTBI

Abstract: Standard auditory oddball ERPs are not sensitive enough to detect and/or quantify subtle objective neuropsychological changes in selected MTBI patients, especially those with traumatic MRI brain lesions. More complex auditory or other oddball paradigms have to be tested in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
(15 reference statements)
0
13
1
Order By: Relevance
“…At the cortical and cognitive levels of the central auditory pathway, few studies have looked at later obligatory, sensory responses such as the cortical auditory evoked potential (or the long latency response) but a great number of studies used cognitive processing potentials such as the P3. Results from auditory P3 studies that have included individuals with mTBI have also been mixed, with some studies showing that P3 results do not differentiate between mTBI and control groups, [50][51][52] but others have demonstrated significant changes in P3 latency and/or amplitude in groups with mTBI. [53][54][55][56] There is considerable variability in patient and injury demographics as well as in methodology of the P3 studies, which may contribute to whether group differences are found.…”
Section: Electrophysiologic Evaluation and Evidence Of Central Auditomentioning
confidence: 99%
“…At the cortical and cognitive levels of the central auditory pathway, few studies have looked at later obligatory, sensory responses such as the cortical auditory evoked potential (or the long latency response) but a great number of studies used cognitive processing potentials such as the P3. Results from auditory P3 studies that have included individuals with mTBI have also been mixed, with some studies showing that P3 results do not differentiate between mTBI and control groups, [50][51][52] but others have demonstrated significant changes in P3 latency and/or amplitude in groups with mTBI. [53][54][55][56] There is considerable variability in patient and injury demographics as well as in methodology of the P3 studies, which may contribute to whether group differences are found.…”
Section: Electrophysiologic Evaluation and Evidence Of Central Auditomentioning
confidence: 99%
“…A common effect of TBI is reduced amplitude and/or increased latency of the P300 recorded from patients compared to control subjects. However, patients with mild TBI do not exhibit abnormal P300s in some studies (Potter et al, 2001;Sivák et al, 2008), but in other studies they do (Alberti et al, 2001;Segalowitz et al, 2001). Von Bierbrauer and Weissenborn (1998) recorded auditory P300s from 15 patients with mild TBI at four time points post-injury: 24 h, 1 week, 3 and 8 weeks.…”
Section: Long-latency Responses (Llrs) In Assessments Of Tbi Patientsmentioning
confidence: 97%
“…Such findings indicate that differentiating between acute and chronic mild TBI with regard to post-injury symptoms may be difficult. However, studies assessing response times (RTs) and scalp-recorded eventrelated potentials (ERPs) show promise in differentiating between neurologically-healthy controls and individuals with acute and chronic mild TBI, suggesting that RTs and ERPs may be sensitive to subtle cognitive disruptions not detected by traditional neuropsychological measures Keren et al, 1998;Pontifex et al, 2009;Sarno et al, 2006;Sivák et al, 2008). The primary objective of the present study was to test the possibility that individuals with mild TBI would show slowed RTs and attenuated electrophysiological signals relative to controls on a task requiring conflict monitoring and conflict adaptation.…”
Section: Introductionmentioning
confidence: 98%